Perbandingan Kemampuan Siswa Dengan Test Score Equating - Zainal Abidin Koemadji (Jurnal Matematika, Statistika dan Komputasi, 2016)
Ability parameters in item response theory will invariant in group of items, in other words, two different respondent with two test with known parameters will have ability estimation on the same scale. Equating of these different tests will give the equivalence of the tests. This paper gives examples on how to perform the equating.